KARAKTERISTIK METADATA PADA SHARING FILE DI MEDIA SOSIAL UNTUK MENDUKUNG ANALISIS BUKTI DIGITAL - Dimas Pamilih Epin Andrian; Dhomas Hatta Fudholi; Yudi Prayudi (STMIK Sinar Nusantara, 2021)
Metadata is information in a file which its contents are an explanation of the file. Metadata contains information about the contents of data for file management purposes. In various cases involving digital evidence, investigators can uncover a case through the metadata file. Problems that arise when file metadata has changed or deleted information, for example, the moment that a file is shared via social media. Basically, all of the shared files through social media will experience changes in metadata information. This study conducted detailed analysis of changes in metadata information and hex dump values to determine the changing characteristics of metadata files shared in social media. This research method applied a comparison table to see the details of changes in metadata values from all files and social media as research objects. The results of this study are expected to have contribution for forensic analysts to identify the shared metadata characteristics of files in social media. As a result, later, the source of shared files in social media will be known. Moreover, it is expected from these findings that forensic analysts can explore the social media used by the cybercrime perpetrators.